Pengaruh Norma Subjektif, Machiavellianisme, Kolektivisme, Dan Etika Terhadap Niat Melakukan Pengungkapan Kecurangan (Whistlebllowing) - Aurelius Ama (Universitas Nusa Putra, 2022)
This study aims to determine the effect of subjective norms, machiavellianism, collectivism, and ethics on intentions to disclose fraud. The population in this study is the State Civil Apparatus (ASN). The sampling method used in this study was selected using Porposive Sampling. The data collection method used a questionnaire. Data testing is done by testing the validity, reliability testing. While the hypothesis test was carried out with multiple nilier regression analysis with the help of SPSS 20.0 software. The results of this study indicate that (1) subjective norms have a positive effect on the intention to disclose fraud (2) Machiavellianism has a negative effect on the intention to disclose fraud (3) Collectivism has a positive effect on the intention to disclose fraud (4) Ethics has a positive effect on the intention to disclose fraud.